Artificial Intelligence Sebagai Sarana Peningkatan Literasi Digital dan Berpikir Kritis Bagi Siswa Sekolah SMA Swasta Cinta Budaya Medan - Syanti Irviantina; Kristian Telambanua; Florida N. Damanik; Erlanie Suparnap; R. A. Fattah Adriansyah (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
This activity aims to enhance digital literacy and critical thinking skills among students of SMA Swasta Cinta Budaya Medan through the use of Artificial Intelligence (AI) technology. The program was implemented as a one-day training session covering basic AI concepts, interactive discussions on AI applications in learning, and hands-on practice with AI-based tools such as ChatGPT and Grammarly. A total of 44 students from grades X to XII participated in the activity. Evaluation through pretest and posttest revealed a significant improvement in students’ understanding, with the average correct answers increasing from 68% to 85%. These results demonstrate that the training approach combining theory, discussion, and practical exercises effectively introduces AI to boost learning productivity and foster critical thinking skills.